Teacup House - Meet the Twitches - Scott, Hayley (Usborne, 2018)
Open up the Teacup House, a playful new full-colour series featuring little rabbit heroes with big dreams! Meet the Twitches, four tiny toy rabbits who live inside a beautiful Teacup House. Stevie loves playing with the Twitches, but she has no idea just how special they are ... because they only come alive when she isn't looking!